Digit ratio (2D:4D) and salivary testosterone, oestradiol and cortisol levels under challenge: Evidence for prenatal effects on adult endocrine responses. Issue 8 (August 2015) - Crewther, Blair; Cook, Christian; Kilduff, Liam; Manning, John
Abstract Background Digit ratio (2D:4D) is a marker for prenatal sex steroids and a correlate of sporting performance. This association may exist because low 2D:4D is linked to high prenatal levels of testosterone (T) and low oestrogens (E). It was recently suggested that low 2D:4D, and particularly low right-left 2D:4D (or Dr-l), is a marker for T changes in response to physical and aggressive challenges. If correct, this link may in part explain the association between 2D:4D and sports performance. Aims We tested this hypothesis in adults. Study design Three experimental treatments were completed using a randomised, cross-over design; (i) cycle sprints plus an aggressive video (S + V), (ii) aggressive video plus cycle sprints (V + S), and (iii) a control session. Subjects 24 healthy adults (12 men and 12 women). Outcome measures Salivary T, oestradiol (E2) and cortisol (C) levels were measured on six occasions across each session and pooled for analysis. Results The S + V treatment was associated with a rise in T and C levels, and Dr-l was significantly and negatively correlated with T and E2 with these effects confined to men. The right 2D:4D and Dr-l were also negatively correlated with the T/C ratio and Dr-l negatively related to the E2/C ratio in men during the S + V treatment. Conclusions We suggest that the hormonal responses to a challenge are programmed by prenatal levels of T and E with possible links to sporting performance in adulthood.